Influencia prosódica en la espirantización de las oclusivas sonoras del castellano de la ciudad de Lima (Perú) - Elias-Ulloa, José (2022)
This article studies the role that stress, and the word-initial syllable has on the spirantization of the intervocalic voiced stops in the Spanish of Lima. Through the analysis of how frequently the stop and approximant allophones of the voiced stops occur and intensity ratio measurements of those allophones, the study found out that there is an asymmetry between the spirantization patterns of non-velar and velar stops. It was also found out that the interaction between stress and the word-initial syllable can inhibit the spirantization of /b, d/ up to a certain degree, and that stress can increase the amount of constriction of their approximant allophones, [?, ð]. Those same prosodic factors do not have any effect on the spirantization of /?/. It regularly surfaces as the velar approximant, [?], in intervocalic environments.